Helping faculty find the balance: Communicating with students with disabilities. Issue 9 (April 2016) - Meeks, Lisa M.; Jain, Neera R.
Abstract : Last month's Coalition Corner discussed possible consequences when students with disabilities lack effective communication skills, but what happens when the fault lies with faculty communication? To avoid situations that adversely affect students, communication around disability matters requires clarity and understanding of basic principles. Disability services providers can assist their faculty through training and written guidance. Here are our top four strategies for improving faculty and administrator communication.